Producing CePowders By (LICVD)Process and Using TEA-Co2 Laser - Mazher, S. N.; Karim, G. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this research , Aprocess ( LICVD) was used for producing silicon nitride powders with chemical compositon Si3N4 ,by using TEA-Co2 Laser to induc reaction in the gas phase, NH3 was used as on additive to SiH4. Reactant gases that were vibrationaly heated by absorbing energy emitted from TEA-Co2 Laser decomposes throug coillsion assisted multiple photon dissociation causing Si3N4 powders. By the dependence of the LICVD process on varios parameters such as Laser intensity , total gas pressure, partial pressures of SiH4 and NH3 were investigated. Dissociation rate as a function of Laser intensity and pressure was investigated. The powders obtained exhibit various colors from brown which is rich in Si to white.This explains that LICVD SiN powders do not have a fixed stoichiometry but depend on the processing parameters, such as SiH4/NH3 ratio.